Translanguaging practices in Indonesian multilingual classrooms: pedagogical implications for inclusive education - Dian Firdha Utami (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Indonesia’s multilingual educational landscape, characterized by the coexistence of Bahasa Indonesia, regional languages, and English, presents both opportunities and structural tensions for inclusive learning. Objective: This study investigates how translanguaging practices function interactionally, pedagogically, and ideologically in Indonesian primary and secondary multilingual classrooms. Method: Using a multi-site qualitative case study design, the research analyzes 72 hours of classroom recordings, pedagogical documents, interviews, and ethnographic field notes through interactional sociolinguistics, translanguaging theory, and critical discourse analysis. Results: The findings show that translanguaging operates as an interactional scaffold that enhances conceptual clarification and redistributes classroom participation. Planned multilingual pedagogical design significantly increases epistemic engagement and reduces participation asymmetry. At the ideological level, translanguaging partially renegotiates symbolic hierarchies that privilege Bahasa Indonesia and English while revaluing regional languages as epistemic resources. Implication: These findings indicate that translanguaging can serve as a powerful pedagogical and ideological strategy for fostering inclusive learning by enhancing participation, reshaping language hierarchies, and legitimizing multilingual knowledge practices in classrooms. Novelty: The novelty of this study lies in its integrative analytical model that links micro-level discourse patterns, pedagogical design structures, and macro-level language ideologies within a unified framework for inclusive education in Southeast Asian multilingual contexts.